Super-Resolution Microscopy and Single-Molecule Tracking Reveal Distinct Adaptive Dynamics of MreB and of Cell Wall-Synthesis Enzymes - Dersch, Simon; Mehl, Johanna; Stuckenschneider, Lisa; Mayer, Benjamin; Roth, Julian; Rohrbach, Alexander; Graumann, Peter L. (Frontiers in Microbiology, 2020)
The movement of filamentous, actin-like MreB and of enzymes synthesizing the bacterial cell wall has been proposed to be highly coordinated. We have investigated the motion of MreB and of RodA and PbpH cell wall synthesis enzymes at 500 ms and at 20 ms time scales, allowing us to compare the motion of entire MreB filaments as well as of single molecules with that of the two synthesis proteins. While all 3 proteins formed assemblies that move with very similar trajectory orientation and with similar velocities, their trajectory lengths differed considerably, with PbpH showing shortest and MreB longest trajectories. These experiments suggest different on/off rates for RodA and PbpH at the putative peptidoglycan-extending machinery (PGEM), and during interaction with MreB filaments. Single molecule tracking revealed distinct slow-moving and freely diffusing populations of PbpH and RodA, indicating that they change between free diffusion and slow motion, indicating a dynamic interaction with the PGEM complex. Dynamics of MreB molecules and the orientation and speed of filaments changed markedly after induction of salt stress, while there was little change for RodA and PbpH single molecule dynamics. During the stress adaptation phase, cells continued to grow and extended the cell wall, while MreB formed fewer and more static filaments. Our results show that cell wall synthesis during stress adaptation occurs in a mode involving adaptation of MreB dynamics, and indicate that B. subtilis cell wall extension involves an interplay of enzymes with distinct binding kinetics to sites of active synthesis.